A genetic assessment of a successful seagrass meadow (Posidonia australis) restoration trial. (28th January 2013) - Sinclair, Elizabeth A.; Verduin, Jennifer; Krauss, Siegfried L.; Hardinge, Jethro; Anthony, Janet; Kendrick, Gary A.
Summary Seagrass meadows are in decline globally. Although numerous experimental methods have been implemented to restore meadows, few have been successful in the long term. Poor decisions on the sourcing of transplants from donor sites, including poor genetic integration and/or low genetic diversity, may impact on restoration success. However, despite evidence to suggest a positive association between genetic diversity and ecological resilience, there is usually little or no input from genetic data to inform on the genetic management of ecological restoration. Cockburn Sound has seen a 77% decline in seagrass cover since 1967. A transplant trial was conducted between 2004 and 2008 with sprigs of Posidonia australis being planted into a bare sand area. Survival was monitored annually, and in 2012, we compared genetic diversity in this transplant area with the original donor site. Genetic diversity in the restored meadow was very high and comparable to the donor site, with no genetic differentiation detected. The high level of genetic diversity and choice of site may have played an important role in the success of this restoration trial. The observed natural recruits around the site after establishment of transplants suggest that local restoration efforts may improve seafloor habitat and facilitate natural expansion of the meadow.